ANALISIS KESULITAN BELAJAR IPA PADA MATERI ENERGI ALTERNATIF KELAS IV SEKOLAH DASAR - Sinkha Arza Khaq; Fadila Nur Rohmah; Mutiara Triana Zain; Cindy Febiana; F. Shoufika Hilyana (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
This research aims to analyze the types of science learning difficulties, describe the factprs that cause science learning difficulties, describe alternative solutions to science learning difficulties using alternative energy sources in class IV students at SDN 2 Gemiringlor for the 2023/2024 academic year, totaling 21 students. This research is a qualitative research. The data collection techniques used were observation, interviews, and documentation. The results of the research show that (1) the types of difficulties experienced by students are difficulties interpreting, exemplifying, classifying, inferring, and explaining, (2) the casual factors are internal factors and external factors, and (3) alternative solutions for students, specifically practicing learning and explaining the material in their own language, getting used to studying regularl, getting used to summarizing the material, and for teachers, giving advice to students who encounter difficulties, using a variety of learning methods and using maps concept of learning means of learning.